Modeling and Forecasting of Inflation in Ghana: SARIMA Approach - Emmanuel Dodzi Kutor Havi (European Scientific Journal, ESJ, 2023)
This study aimed at modeling and forecasting inflation rate in Ghana using seasonal autoregressive integrated moving average model with monthly consumer price index data from January 2012 to December 2022. Using Philip-Parron unit root test, the result showed that the time series data was stationary in its first difference, showing that consumer price index was integrated of the first order. Also, from the seasonal graph, seasonality was observed in the data. The correlogram of ACF and PACF helped to select appropriate lag for p and q. Box-Jenkins procedure was applied to identify the appropriate model that fit the data. From the Box-Jenkins procedure, SARIMA(1,1, 1)(1,1,1)12 model was identify as the best model to forecast inflation rate. From the forecast graph, the inflation will begin to rise from the second quarter of 2023. However, the forecast from January to March, 2023 inflation rates were 54.9, 56.5 and 50.2, respectively. Therefore, it is highly likely that Ghanaian inflation will be rising in the subsequent months based on 2012 to 2022 Consumer Price Index. The appropriate authorities should put monetary and fiscal policy measures in place to moderate the envisage rise in inflation.